Dampak Pemekaran Kabupaten Kolaka Timur Terhadap Kemajuan Ekonomi Masyarakat Infrastruktur Daerah - Risky Guswari; Naidah Naidah; Ismail Rasulong (Economics and Digital Business Review, 2025)
Abstract This study aims to determine the impact of the regional expansion of Kolaka Timur Regency on community economic development and regional infrastructure improvement. The regional expansion was carried out to enhance the effectiveness of public services and accelerate economic growth in previously underserved areas. This research employs a descriptive qualitative approach with data collected through in-depth interviews, field observations, and documentation. Informants include local government officials, community leaders, and residents. The findings indicate that the expansion of Kolaka Timur Regency has had a positive impact on increasing economic activity, creating job opportunities, and introducing various community empowerment programs. In terms of infrastructure, there have been improvements in roads, public facilities, as well as health and education services. However, challenges such as budget limitations, human resource capacity, and geographical access remain obstacles. Overall, the regional expansion contributes to accelerating regional development, although improvements in several aspects are still needed. Keywords: Regional Expansion, Community Economy, Infrastructure, Regional Development